Analytical Methods for Brassinosteroid Analysis: Recent Advances and Applications - Oklestkova, Jana; Kvasnica, Miroslav; Strnad, Miroslav (Plant & cell physiology, 2024)
Brassinosteroids (BRs) are plant steroidal hormones that play crucial roles in plant growth and development. Accurate quantification of BRs in plant tissues is essential for understanding their biological functions. This study presents a comprehensive overview of the latest methods used for the quantification of BRs in plants. We discuss the principles, advantages and limitations of various analytical techniques, including immunoassays, gas chromatography-mass spectrometry and liquid chromatography-tandem mass spectrometry that are used for the detection and quantification of BRs from complex plant matrixes. We also explore the use of isotopically labeled internal standards to improve the accuracy and reliability of BR quantification.
Keywords: Immunoassays; Plants; Chromatography, Liquid; Chemical synthesis; tandemová hmotnostní spektrometrie; imunoanalýza; regulátory růstu rostlin; plynová chromatografie s hmotnostně spektrometrickou detekcí; Quantification; chromatografie kapalinová; Chromatography; rostliny; Gas Chromatography-Mass Spectrometry; brassinosteroidy; Plant Growth Regulators; Mass spectrometry; Immunoassay; Tandem Mass Spectrometry; Brassinosteroids